2018
DOI: 10.7717/peerj.5009
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin significantly influences seed germination and seedling growth ofStevia rebaudianaBertoni

Abstract: BackgroundMelatonin (MEL) is a signaling molecule in plants that affects developmental processes during vegetative and reproductive growth. Investigations have proved that exogenously applied MEL also has the potential to improve seed germination and plant development.MethodsIn the present study, seeds of stevia, a species with a very low germination rate, were germinated on an agar gel (AG) containing MEL at various concentrations (5, 20, 100, and 500 µM) in light. Seeds germinated on AG without MEL were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 71 publications
6
23
0
1
Order By: Relevance
“…This indicator further validates the above conclusions. Our findings are broadly consistent with those of Simlat et al [49], who reported that the lowest melatonin concentrations examined (5 and 20 μM) exerted a significantly positive effect on Stevia seed germination compared with the 100 and 500 μM treatments. Previous studies have found that melatonin application significantly increased osmopriming effects, such that 50 μM melatonin achieved maximal results [43].…”
Section: Discussionsupporting
confidence: 93%
“…This indicator further validates the above conclusions. Our findings are broadly consistent with those of Simlat et al [49], who reported that the lowest melatonin concentrations examined (5 and 20 μM) exerted a significantly positive effect on Stevia seed germination compared with the 100 and 500 μM treatments. Previous studies have found that melatonin application significantly increased osmopriming effects, such that 50 μM melatonin achieved maximal results [43].…”
Section: Discussionsupporting
confidence: 93%
“…These results demonstrated that the effect of MT on cotton seeds is closely associated with its concentration and 100 μM MT was defined as the optimum concentration to promote cotton seed germination under drought stress. These findings are in accordance with Simlat et al (2018) , who demonstrated that a low concentration of exogenous MT promoted seed germination, while treatments with a high dose of MT inhibited seed germination. Previous studies reported that soaking seeds in exogenous MT (20 and 100 μM) alleviated drought-induced germination inhibition by advancing the antioxidant defense system ( Ding, Liu & Zhang, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…Simlat et al . 16 found that a low dose of MT (5 and 20 µM) significantly improved the seed germination and properties of Stevia rebaudiana Bertoni plantlet, while treatments with a higher dose showed an obvious inhibitory effect. Furthermore, Li et al .…”
Section: Discussionmentioning
confidence: 94%
“…As a pleiotropic molecule with various functions in animals and plants, MT has been shown to be an efficient growth regulator in plants 12,13 . Several studies have demonstrated that, lower dose of MT ( < 10 μM) can stimulate the growth of maize plants and the germination of cucumber seeds under cold stress 1416 . In cucumber, seed priming with MT promotes lateral root formation and seed germination under water-stress conditions 17 .…”
Section: Introductionmentioning
confidence: 99%